1980
DOI: 10.1136/sti.56.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of infection by serotypes D to K of chlamydia trachomatis.

Abstract: Following the parallel of gonorrhoea, it seems that the use of contact tracers may be an effective method for controlling chlamydial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Another very interesting finding in this study is that IFN-␥ KO mice intranasally infected with MoPn exhibited endocar-ditis and pericarditis. Endocarditis caused by C. trachomatis infection has been reported in previous clinical studies (6,7,24,33). Several individual cases of chlamydial endocarditis caused by C. pneumoniae have also been documented in clinical practice over the past decade (5,13,20).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another very interesting finding in this study is that IFN-␥ KO mice intranasally infected with MoPn exhibited endocar-ditis and pericarditis. Endocarditis caused by C. trachomatis infection has been reported in previous clinical studies (6,7,24,33). Several individual cases of chlamydial endocarditis caused by C. pneumoniae have also been documented in clinical practice over the past decade (5,13,20).…”
Section: Discussionmentioning
confidence: 85%
“…Chlamydiae, especially Chlamydia pneumoniae, are highly associated with cardiovascular diseases including atherosclerosis (8,11,17,21,(29)(30)(31)(32). C. trachomatis, although rare, is a cause of bacterial endocardial and myocardial diseases (6,7,12,24,27,28,33). Thus far, however, few experimental studies have been carried out to directly investigate the relationship between C. trachomatis and cardiovascular pathology and to examine the protective factors involving host defense against cardiac chlamydial infection.…”
mentioning
confidence: 99%
“…Persistent excretion of infectious organisms is well documented in genital chlamydial infections, particularlyin women (Dunlop, Darougar & Treharne, 1980). It is therefore interesting that ocular complications in adults are so uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies with newly developed cell culture methods for isolation of C. trachomatis have shown that there is a large reservoir of genital chlamydia in the genital tract of young, sexually promiscuous populations in Western societies (Richmond & Oriel, 1978;Dunlop, Darougar & Treharne, 1980), and prospective studies suggest that up to one in three babies born to mothers with chlamydiainfected cervices may develop a chlamydial ophthalmia in the neonatal period (Alexander et al 1977;Schachter et al 1979). Little information is available, however, on the risk of paratrachoma developing in adults with a genital chlamydial infection.…”
Section: Introductionmentioning
confidence: 99%
“…As with Chlamydia psittaci, Chlamydia trachomatis infections can involve one or more heart valves in patients with previously normal or abnormal valves (62)(63)(64)(65). In addition, a case of endocarditis associated with Chlamydia trachomatis in a patient with a congenital ventricular septal defect and no evidence of valvular disease has also been reported (66).…”
Section: Chlamydiae and Endocarditismentioning
confidence: 99%